Hedging Rules-Based Optimal Reservoir Operation Using Bat Algorithm - Jamshidi, Javad; Shourian, Mojtaba (Water resources management, 2019)
In this study, optimal operation of a reservoir by incorporation of the hedging policy and the Bat Algorithm (BA) is investigated. The deficit in water supply by the dam is minimized as the objective function and the optimal monthly releases from the reservoir are determined and compared in three hedging-based operation rules. In the first rule, which has a single decision variable, a constant monthly release is considered for all 240 months of the operation period. In the second scenario, one fixed release is determined for each month of the year and is repeated in successive operating years which results 12 decision variables for the problem. In the third rule, all monthly releases are varied as the decision variables resulting 240 unknowns for the problem. The developed models are utilized for the Zhaveh reservoir in west of Iran. Results show that while BA is a suitable easy going algorithm to be applied for optimal reservoir operation planning, the amount of water deficit is lower when a higher degree of freedom is defined for the operating rules as the values for the objective function are 105.3, 102.8, and 80.5 for the first to the third scenarios, respectively. Afterward, the results using the hedging rules are compared with the standard operating policy (SOP) and it is found that the reservoir performance is more desirable in satisfying water demands when the hedging policy is applied.